2016
DOI: 10.1039/c6ra01126h
|View full text |Cite
|
Sign up to set email alerts
|

Developing radiation tolerant polymer nanocomposites using C60as an additive

Abstract: The attenuation of alpha particles is modelled using Monte-Carlo N-Particle Extended software. Using tandem Van de Graaff accelerator tests, it is shown that doping with C60fullerene can significantly enhance the lifetime of polymers in alpha radiation environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Christian et al [3] reported the development of radiation resistant C 60 -doped polyvinyl alcohol (PVA) films. These films could withstand approximately seven times more α radiation than undoped PVA or PE films when tested using an alpha particle accelerator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Christian et al [3] reported the development of radiation resistant C 60 -doped polyvinyl alcohol (PVA) films. These films could withstand approximately seven times more α radiation than undoped PVA or PE films when tested using an alpha particle accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 10 wt.% of LiBH4 was mixed with C60 and THF in an argon glovebox. The THF was then removed under vacuum and the resultant powder was annealed at 300 o C for 1 h[3,15].…”
mentioning
confidence: 99%